Assessing the Influence of Mobility Behavior on the Covid-19 Transmission: A Case in the Most Affected City of Indonesia - Umar, Najirah; Gani, Hamdan; Zuhriyah, Sitti; Gani, Helmy; Zhipeng, Feng (ILKOM Jurnal Ilmiah, 2022)
An emerging outbreak of Covid-19 has now been detected across the globe. Given this pandemic condition, the robust estimation reports are urgently needed. Therefore, this study aims to analyze the impacts of community mobility (before, during, and after the lockdown period) on the spread of the Covid-19 in Jakarta, Indonesia. The secondary data was derived from surveillance data for Covid-19 daily cases from the Health Office of DKI Jakarta Province and the Ministry of Health. The community mobility indicators were retrieved from the Google website. Our results showed that in the pre-lockdown period, the Covid-19 daily cases rapidly increased, while community mobility significantly dropped. The increasing number of Covid-19 daily cases was significantly affected by the number of Covid-19 tests per day rather than community mobility. During the restriction period, the number of Covid-19 tests per day, and community mobility statistically affected the decreasing number of Covid-19 daily cases. Meanwhile, after the lockdown period, the number of Covid-19 daily cases rapidly increased, which significantly has a direct relationship with the increasing level of community mobility. Overall, community mobility and the number of tests per day are the essential variables that explain the number of Covid-19 daily cases in Jakarta, Indonesia. Additionally, this study did not observe any impact of average air temperature and air pollution on the spread of Covid-19. This study figures out that community mobility could potentially explain the progression of Covid-19.